1987
DOI: 10.3171/jns.1987.66.5.0729
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tumor plasminogen activator with peritumoral cerebral edema

Abstract: Extracts from 15 human cerebral tumors were tested by a fibrin-plate plasminogen-dependent assay for levels of tumor plasminogen activator (TPA) activity. The TPA activity was correlated with the amount of perineoplastic edema as quantified on computerized tomography (CT) brain scanning. Analysis of the results showed a correlation coefficient of 0.72 when all tumors were included. Analysis of the nine tumors with the highest TPA levels showed a correlation coefficient of 0.96. One metastatic tumor had the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…[31] Increased vascular endothelial growth factor detected by immunostaining correlated with the degree of edema in 37 tumors examined by Goldman, et al [14] The volume of peritumoral edema in 15 meningiomas correlated with tumor plasminogen activator content in a study by Quindlen and Bucher. [32] Hirashima and coworkers [15] found that platelet-activating factor immunostaining correlated with peritumoral edema in 31 patients. The quantity and location of peritumoral edema was associated with induction of pial blood supply by meningiomas in a recent paper by Bitzer and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Increased vascular endothelial growth factor detected by immunostaining correlated with the degree of edema in 37 tumors examined by Goldman, et al [14] The volume of peritumoral edema in 15 meningiomas correlated with tumor plasminogen activator content in a study by Quindlen and Bucher. [32] Hirashima and coworkers [15] found that platelet-activating factor immunostaining correlated with peritumoral edema in 31 patients. The quantity and location of peritumoral edema was associated with induction of pial blood supply by meningiomas in a recent paper by Bitzer and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other authors suggested that an activation of local fibrinolysis [1,2,13,14] is one of the bleeding mechanisms. In addi tion, Tucker et al [15] showed that meningio ma cells in culture produced plasminogen ac tivators which have been considered as a pos sible reason of haemorrhagic events.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bruce et al [13] found that incubation of their glioma cells with dexamethasone reduced the permeability factor. Recently, some correlation of tumor plasminogen activator (TPA) with peritumoral brain edema was indicated in the relationship between TPA levels in specimens of human brain tumors and the amount of peritumoral edema shown in computerized tomography [29]. The factor in SUP-C from C6 gliomas, however, seems to be different from TPA, even if TPA is included in the SUP-C fraction.…”
Section: Discussionmentioning
confidence: 99%